2004
DOI: 10.1128/jvi.78.20.11187-11197.2004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Proteins Associated with Murine Cytomegalovirus Virions

Abstract: Proteins associated with the murine cytomegalovirus (MCMV) viral particle were identified by a combined approach of proteomic and genomic methods. Purified MCMV virions were dissociated by complete denaturation and subjected to either separation by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and in-gel digestion or treated directly by in-solution tryptic digestion. Peptides were separated by nanoflow liquid chromatography and analyzed by tandem mass spectrometry (LC-MS/MS). The MS/MS spectra obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
126
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(136 citation statements)
references
References 68 publications
9
126
0
1
Order By: Relevance
“…Recent work has shown that host-derived actin is incorporated into the PRV virion and becomes an integral part of the outer tegument layer [42,43]. Virion-associated actin has been reported in other herpesviruses [44][45][46][47][48][49] and other enveloped viruses, including paramyxovirus, retrovirus and rhabdovirus [50][51][52][53][54]. But why do herpesviruses contain F-actin in the virion?…”
Section: Actin Is a Component Of The Herpesvirus Virionmentioning
confidence: 99%
“…Recent work has shown that host-derived actin is incorporated into the PRV virion and becomes an integral part of the outer tegument layer [42,43]. Virion-associated actin has been reported in other herpesviruses [44][45][46][47][48][49] and other enveloped viruses, including paramyxovirus, retrovirus and rhabdovirus [50][51][52][53][54]. But why do herpesviruses contain F-actin in the virion?…”
Section: Actin Is a Component Of The Herpesvirus Virionmentioning
confidence: 99%
“…In recent years, mass spectrometry (MS)-based analysis has been used to identify the composition of different herpesviruses (2,3,7,13,25,27,28,31,41,53,55,58). Within rhadinoviruses, KSHV (3,58), rhesus monkey rhadinovirus (RRV) (41), and murid herpesvirus 4 (MuHV-4) (7) extracellular virions have been analyzed using this approach.…”
mentioning
confidence: 99%
“…In addition to IAV, AnxA1 is found associated with several other viruses [114][115][116][117][118][119][120][121][122]. Interestingly, no indications so far suggest that the viruses rely on its immune-modulating capacity to facilitate virus entry, although the AnxA1 receptor FPR2 is involved in IAV replication [123].…”
Section: Annexins and The Host/pathogen Interfacementioning
confidence: 99%